Evaluasi Maturity Level Manajemen Layanan Teknologi Informasi menggunakan Framework ITIL v3 Domain Service Operation pada 24Slides Corporation - Andra Bayu Febriant; Yusi Tyroni Mursityo; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
24Slides is a multinational company in the field of digital outsourcing that serves presentation redesigns in the form of powerpoints. This company has information technology services to facilitate the operation of internet-based companies. There are a number of reasons for evaluating IT service management on 24Slides because the company has been operating for seven years and should have received an evaluation. In addition, the distance between the two different continental offices makes the company's operations interesting to evaluate. And the last one is due to the fact that no audit has been conducted. This study uses the Information Technology Infrastructure Library (ITIL) framework V3 domain service operation to measure maturity levels, gap analysis, and formulate recommendations for improvement of 24Slides. The questionnaire used is based on University and Colleges Information Systems Association (UCISA). The conclusion obtained in this study is the average score of the maturity level that is worth 2.6 and falls into the repeatable category with a gap of 0.8. The value of the maturity level 2.6 can be interpreted as a basic processes and activities are established and there is a level of discipline and adherence in the 24Slides company. And a gap value of 0.8 means the expectation of 24Slides is greater than what is currently experienced. From the low indicators and by discussions with respondents, can be used as findings to formulate recommendations. The focus of recommendation is run the entire basic processes and carry out documentation and standardization in order to achieve level 3, namely defined level.